CREATION AND MANAGEMENT OF A REAL ESTATE CADASTRAL INFORMATION BASE - Abdiraxmatov Nuriddin Abdiraxmatovich,; Mirzayev Jonibek Oltiyevich,; Hamdamova Dildora Murodulla qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation.  This  paper  analyzes  the  process  of  creating  an  information resource  for  real  estate  cadastre,  its  importance  and  effectiveness.  The  real  estate cadastre is an important information base for the protection of property rights, property management and the calculation of state taxes. The paper examines the application of modern technologies for collecting, storing, updating and using cadastral information, including  geographic  information  systems  (GITS)  and  digital  platforms.  It  also analyzes the problems that arise in the process of creating and managing information resources, and ways to solve them. As a result, the possibilities of ensuring legality in the real estate sector, developing the real estate market, and improving the quality of public  administration  through  the  formation  of  an  effective  cadastral  information system are determined.